Islamic Educational Institution Policies Based on Creative Economic the Asean Era Economic Community - Syam, Aldo Redho; Arifin, Syamsul (EDUKASI: Jurnal Pendidikan Islam, 2018)
Competition in the era of Asean Economic Community is increasingly stringent, leading the Islamic educational institutions not only oriented to academic aspects but also on other aspects, including the economic aspects. The concept of Islamic educational institutions today should lead to the establishment of creative Islamic educational institutions, especially creative-based economies. Islamic education institutions today are no longer sticking to conventional learning methods to provide knowledge to the human resources of Islamic education, but to apply learning methods while learning, which is expected to guide the human resources of Islamic education to develop creativity, innovation, and productivity. Looking at the prospects that are needed at this time, the Islamic educational institutions are expected to immediately change the orientation of Islamic education in the institution, in order to produce excellence in social, cultural, economic, and etc.